Counselors’ Multicultural Competence in Working with Male Counselees - Ahmad Abdul Hakim; Andi Wahyu Irawan; Andi Retno Budiarty Nazaruddin (Pamomong: Journal of Islamic Educational Counseling, 2025)
This study investigates how multicultural competence is understood and enacted by a school counselor, identifies the challenges experienced when working with male counselees from different cultural backgrounds, and examines the adaptive strategies employed to enhance counseling effectiveness and inclusivity at Istiqomah Muhammadiyah 4 Vocational High School in Samarinda. Using a qualitative fieldwork design, the study involved one female counselor and two male counselees from Banjar and Dayak ethnic backgrounds. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using ATLAS.ti through open, axial, and selective coding. The findings show that the counselor practices multicultural competence through culturally sensitive understanding, value-based and logic-oriented communication, active family involvement as an ecological support, and contextual adaptation of Western approaches such as CBT and SFBC to local and Islamic principles, including adab, maslahah, and the prohibition of khalwat. The main challenges include restrictive masculinity norms that limit emotional expression, stigma toward counseling, and institutional pressures for rapid problem resolution at school. Adaptive strategies based on relational empathy, cross-system collaboration, and culturally embedded interventions gradually enhanced counselees’ engagement, comfort, and openness. The study indicates that multicultural competence is a dynamic process requiring ongoing self-awareness, ethical sensitivity, and cultural responsiveness. The small sample and single research site limit the generalizability of these results, so future studies should involve more diverse cultural and gender groups, multiple school settings, and mixed-method or comparative designs to further test and refine the proposed adaptive multicultural counseling model.